Exploring the experiences of birth mothers whose children have been diagnosed with fetal alcohol spectrum disorders: a qualitative study. Issue 1 (11th January 2019) - Thomas, Robyn; Mukherjee, Raja
Abstract : Purpose: Fetal alcohol spectrum disorder (FASD) is an umbrella term for a range of conditions that may occur in an individual whose mother drank alcohol during pregnancy. There has been little research into the experience of birth mothers of children with FASD and no published work of this kind in the UK. This is in contrast to a number of studies that have been conducted on foster/adoptive parents. In light of the recent publication in the UK of a mixed methods study on adoptive carers, it is timely to conduct research on birth mothers in the UK. The purpose of this paper is to explore the experiences of birth mothers following a diagnosis of FASD in their children. Design/methodology/approach: An interpretive phenomenological analytical approach was used to generate themes from individual semi-structured interviews of five women who are birth mothers of children with FASD. Findings: Four superordinate main themes and various subthemes were identified. To blame or not to blame captures the tension the mothers experience when considering the cause of their child's condition. Life is a series of battles which describes the struggles the women experience on a crusade with a renewed sense of purpose that captures the process of transformation that occurs, which helps describe the internal and external factors that help the mothers cope. Originality/value: FASD is often described in the literature as being completely preventable with the implication that it is the mother's fault because they drank alcohol during pregnancy. However, a statement like this fails to portray the complexities of the phenomenon of women drinking during pregnancy. Life is difficult for the women for a number of different reasons, yet a sense of hope is present. The mothers have a renewed sense of purpose to do the best they can for their child and to raise awareness of FASD. Understanding their experiences can help service providers better meet the needs of parents and children affected by FASD.